THE COLLATERAL EFFECTS RELATED WITH THE ANDROGENIC PROPERTIES OF THE ANABOLIC STEROIDS IN WISTAR MALE ADULT MOUSE (Fiep Bulletin - online, 2014)
The use of anabolic androgenic steroid (EAA) has been described in many situation as liable of diverse collateral effect diseases. The purpose of this research was analyze the weight alteration that could have occurred on the main organs of the male reproduction system (prostate, epididymis, testicle, seminal vesicle), and on the immunological system in sedentary group of adults male mouse of race Wistar. The animals were divided in two groups : Group 1 with peanut oil injection , Group 2 EAA injection. The EAA (DURATESTON® 5mg/kg) was injected via subcutaneous intersect through the sural triceps on the back paw being alternated between right and left during 10 consecutive days. After that period the animals were sacrificed and the weight of the testicle, prostate, epididymis, seminal vesicle was analyzed and also the blood for immunologic system verification (monocytes, lymphocytes, neutrophil, leukocytes total). Analyzing the results, It was found relevant statistic difference on the weight of the organs prostate, epididymis and, seminal vesicle. In the immunological system it was noticed relevant modifications on the monocytes ( p < 0,05 ) figures. Thought this research it was possible to realize that the 10 days application of Durateston® lead to the weight increase on the seminal vesicle, epididymis, prostate and also on the monocytes figures.
Keywords: Anabolic androgenic steroid (EAA); Immunological system; Male reproductor system